Struktur dan Fungsi Sosial Cerita Rakyat Legenda Putri Runduk di Provinsi Sumatera Utara - Simatupang, Desti Adelia; Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to explain the structure and social function of the folklore of the legend of Putri Runduk in Sibolga Ilir Village. This qualitative research with descriptive method uses data from the folklore of the legend of Putri Runduk in Sibolga Ilir Village. Data were collected through interviews, observations, and data recording, then analyzed with the stages of data description, data classification, and reporting. The results showed that the structure of the folklore legend of Putri Runduk consists of language style, characterization, plot, setting, theme, and mandate, and its social function is as an oral tradition inheritance and educational media. This research is expected to provide a better understanding of the structure and social function of the folklore of the legend of Putri Runduk, and is useful for researchers and people who want to know the cultural values contained in it.